THE LOWER CLASS IN THOMAS GRAY’S “ELEGY WRITTEN IN A COUNTRY CHURCHYARD” - Vivin Afini (Esteem Journal of English Education Study Programme, 2020)
“Elegy Written in a Country Churchyard”, by Thomas Gray is the main source data of this study. It is a poem of reflections – reflections of death, nature, the lots of marginal people, the poor, or the lower class which becomes the subject matter of the study. The objectives are to find out the concept of lower class in social discrimination. It is qualitative research. The research result show that the examples of discrimination found in Stanza 4,8, 10, 12, 13, 14, 16, 17 and 18. In this elegy, the social stratification formed by itself and the system is the closed system. The poor belongs to the lower class and always becones a focus of attention owing to their being wretched, powerless and illiterate. They are actually great in their low quality. All of these traits are beautifully exposed in the poem.